Mathematical modelling in higher education: Evolving research and emerging trends (1980–2023) - Ngu, Pham Nguyen Hong; Nam, Nguyen Danh; Cuong, Le Minh; Thao, Trinh Thi Phuong (Jurnal Infinity, 2025)
Mathematical education in higher education plays a significant role in training future citizens with problem-solving skills to meet professional requirements. One of the trends in teaching mathematics at universities that has received much focus is teaching mathematics through modelling. The article uses the bibliometric analysis method through Bibliometrix and VOSviewer software to analyze 271 publications extracted from the Scopus database to provide an overall picture of mathematics modelling research in higher education from 1980 to 2023. The results indicate that the growth trend of publications is unstable, with a significant increase in the last 5 years. The United States and China are the two leading countries in terms of the number of published publications and citations; Tecnológico de Monterrey (Mexico) is the affiliation with the highest number of publications; the Book series “International Perspectives on the Teaching and Learning of Mathematical Modelling” is the most release source on this topic. The article also analyzes co-occurring keywords and identifies 03 research trends on this topic, including using technology and computer programming in mathematics modelling curriculum for students of technical universities, teaching mathematic modelling in universities, as well as using technology in teaching modelling and STEM education, innovating teaching methods of mathematics modelling and applying information technology in teaching mathematics modelling in pedagogic training programs. This is the first bibliometric study on mathematics modelling. These important research results help scholars interested in this research direction have an overview through useful quantitative information regarding mathematical modelling research in higher education worldwide, thereby developing appropriate research trends.